Symbolic Product Superiority in the Neural Salience of Compensatory Consumption Behavior - Yu, Wenjun; Sun, Zhongqiang; He, Zhihui; Ye, Chuyuan; Ma, Qingguo (Frontiers in Psychology, 2020)
To cope with self-threat being induced by personal setbacks in daily life, compensatory consumption, especially on symbolic product, has been found to do valuable help to resolve discrepancies between ideal and actual self-concept. Conforming to symbolic self-completion theory, current study adopted event-related potentials to explore the objective information processing stages in self-concept-impaired status (the Defeat group) on a neural level. The behavioral results replicated previous findings that the Defeat group gained stronger purchase intention for symbolic products than utilitarian products. The electrophysiological data demonstrated that perceptual difficulties for products in preliminary stage (N1) were steady among conditions, and after that information processing separation emerged. In contrast to the individuals with a draw experience, those with a defeat experience raised highly-focused attention (P2) and eager expectation (N2) for products, especially for symbolic ones. Meanwhile, symbolic (vs. utilitarian) products also evoked higher emotional arousal level and slowed the diminishment of involved attentional resource (late positive potential) at late cognitive processing stage. Taken together, the sequential integration of multiple neural indicators contributes to elucidating the processing stages of compensatory consumption behavior.